Magnetic properties of AlFe2B2 and CeMn2Si2 synthesized by melt spinning of stoichiometric compositions. (20th April 2015) - Du, Qianheng; Chen, Guofu; Yang, Wenyun; Song, Zhigang; Hua, Muxin; Du, Honglin; Wang, Changsheng; Liu, Shunquan; Han, Jingzhi; Zhang, Yan; Yang, Jinbo
Abstract: By suppressing the growth of impurities, a melt spinning method was successfully applied to the synthesis of typical layered CeMn2 Si2 and AlFe2 B2 compounds. X-ray diffraction analysis showed that CeMn2 Si2 and AlFe2 B2 had good purity and crystallized in ThCr2 Si2 - and AlFe2 B2 -type structures, respectively. The differences among three -type structures were also analyzed. The magnetic properties were investigated by magnetic measurements and electronic structure calculations. It was found that the Fe moment of AlFe2 B2 reaches 1.32 μB at 5 K, which fits well with the calculated result of 1.44 μB at 0 K, and that the isothermal magnetic entropy change reaches 7.2 J kg −1 K −1 at 5 T, which shows great potential for room-temperature refrigeration applications.